Penguatan Manajemen Risiko Lembaga Keuangan Syariah Non-Bank dalam Menghadapi Ancaman Cyber Security - Fajar Adhi Kurniawan; Khabib Solihin (Fakultas Syariah dan Ekonomi Islam Institut Pesantren Mathali'ul Falah, 2022)
This research is a qualitative research that discusses the strengthening of risk management non-bank Islamic financial institutions, KSPPS Artha Bahana Syariah Pati Central Java. The sources of data in this study were obtained through focus groups and in depth interviews with KSPPS leaders and related officials. KSPPS Artha Bahana Syariah Pati Central Java develops internet-based digital services to its members in the form of ABS Mobile. The use of digital and internet technology to improve services to members and to gain business effectiveness and efficiency must be accompanied by strengthening risk management to anticipate cyber security threats. The results of the study indicate that the application of risk management at KSPPS Artha Bahana Syariah is related to the threat of cyber security in the form of active supervision by the leadership, the adequacy of policies and procedures for the use of Information Technology, the adequacy of the identification, measurement, control, and monitoring of information technology risks, and the internal control system. on the use of information technology.